2020
DOI: 10.21203/rs.3.rs-37980/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SNPs rs429358 and rs7412 of APOE gene are association with cerebral infarction but not SNPs rs2306283 and rs4149056 of SLCO1B1 gene in southern Chinese Hakka population

Abstract: Background: Apolipoprotein E (ApoE) and solute carrier organic anion transporter family member 1B1 (SLCO1B1) regulate lipid metabolism. However, the relationship between genetic polymorphisms of APOE and SLCO1B1 and cerebral infarction (CI) remains unclear.Methods: A total of 938 CI patients and 1,028 control participants were included in the study. The rs429358 and rs7412 single nucleotide polymorphisms (SNPs) in the APOE gene and rs2306283 and rs4149056 SNPs in the SLCO1B1 gene were analyzed by fluorescence … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that there is a signi cant association between CI and 4 allele 19,20 , and it has been found that the frequency of 4 allele in Asian with CI is higher than that in Caucasian population 20 , and 4 allele carrier is more likely to develop CI in Asian population 21 . In Chinese population, many studies indicated that 4 allele were the risk for the presence of CI [22][23][24] . In our study we found that the frequency of 4 allele in CI group was signi cantly higher than that in control group (P < 0.01) in North China, which was similar to the results of previous studies on Chinese population, suggesting that the frequency of 4 allele is more higher in CI patients 8,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a signi cant association between CI and 4 allele 19,20 , and it has been found that the frequency of 4 allele in Asian with CI is higher than that in Caucasian population 20 , and 4 allele carrier is more likely to develop CI in Asian population 21 . In Chinese population, many studies indicated that 4 allele were the risk for the presence of CI [22][23][24] . In our study we found that the frequency of 4 allele in CI group was signi cantly higher than that in control group (P < 0.01) in North China, which was similar to the results of previous studies on Chinese population, suggesting that the frequency of 4 allele is more higher in CI patients 8,23,24 .…”
Section: Discussionmentioning
confidence: 99%